Effort for Implimentation Go Green System - Johan Pongoh; Gracia Ester Tendean; Evandra Matthew Lae; Indawahyuni Malah; Ferginia Frili Sengka; Novlinda Anatasya Debora Mongkau (Jurnal Syntax Admiration, 2025)
Environmental problems are one of the serious environmental issues that we are facing, with various challenges such as air pollution, environmental pollution, carbon emissions, and excessive use of plastic, which have an impact on us humans. This journal discusses the implementation of the Go Green system as a solution to overcome this problem. Go Green is a movement that focuses on efforts to protect and care for the environment through various actions and efforts, such as saving energy, reducing plastic waste and recycling waste. This research uses participatory methods and interviews, and involves waste recycling and greening practices. The research results show that consistent implementation of the Go Green system can have a positive impact on the environment, reduce pollution and support the sustainability of the earth. With good cooperation and individual responsibility, this system can be a long-term solution for preserving the environment.